2022
DOI: 10.3748/wjg.v28.i6.624
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the diagnostic evaluation of pancreatic cystic lesions

Abstract: Pancreatic cystic lesions (PCLs) are becoming more prevalent due to more frequent abdominal imaging and the increasing age of the general population. It has become crucial to identify these PCLs and subsequently risk stratify them to guide management. Given the high morbidity associated with pancreatic surgery, only those PCLs at high risk for malignancy should undergo such treatment. However, current diagnostic testing is suboptimal at accurately diagnosing and risk stratifying PCLs. Therefore, research has f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ]. Although uncommon, one potential and serious complication of EUS-TA is needle tract seeding (NTS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ]. Although uncommon, one potential and serious complication of EUS-TA is needle tract seeding (NTS) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard of care analysis of the cyst fluid (CEA, amylase, glucose, and cytology) improve the differentiation of PCLs. EUS-FNA of cyst fluid with molecular analysis and nCLE for in vivo endomicroscopy, when indicated (generally PCLs ≥ 2 cm diameter), collectively approach a high (>90%) accuracy for the diagnosis and risk stratification of PCLs [2][3][4][5]9,23]. Data sources [1,3,9,13,14,52,66,72].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have described features observed in specific PCLs using two advanced diagnostics (nCLE and cyst fluid NGS). Both techniques can enhance the diagnostic accuracy of cyst type and advanced neoplasia significantly [108], and they may be considered when radiomics and EUS cyst morphology are indicative of a high-risk PCL [2]. However, these advanced diagnostics are only available in limited centers currently, and large prospective studies are needed before incorporation into guidelines.…”
Section: Advanced and Emerging Diagnostic Tools For Pancreatic Cystic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the two major applications of this technique are diagnosis of cyst type and malignant risk-stratification. Positive cyst fluid cytology is a surgical indication amongst all current guidelines because it is highly specific for lesions harboring advanced neoplasia, although it is of limited sensitivity [ 71 , 72 ] Genomic analysis via NGS of cyst fluid is a well-studied method that lends to improved sensitivity while maintaining high specificity for the diagnosis of mucinous neoplasm and advanced neoplasia. Specifically, the presence of KRAS and GNAS mutations in cyst fluid has enhanced sensitivity and specificity for classifying mucinous lesions when compared with CEA and cytology [ 73 , 74 ].…”
Section: The Future Of Ai and Eusmentioning
confidence: 99%